2009
DOI: 10.1002/art.24648
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of second‐generation ultrasound contrast media in the detection of active sacroiliitis

Abstract: Objective. To determine whether a recently available contrast-enhanced ultrasound (CEUS) technique using secondgeneration microbubbles allows for the detection of active sacroiliitis, and to measure CEUS enhancement depth at the dorsocaudal part of the sacroiliac (SI) joints in healthy volunteers compared with patients with sacroiliitis. Methods. Forty-two consecutive patients (84 SI joints) presenting with a clinical diagnosis of sacroiliitis in 50 SI joints and 21 controls (42 SI joints) were investigated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 28 publications
0
20
0
2
Order By: Relevance
“…This is supported by the inclusion of their findings in the last EULAR recommendations for the contrast agent with respect to healthy subjects [19]. However, the barrier of the costs is still palpable.…”
Section: Introductionmentioning
confidence: 85%
“…This is supported by the inclusion of their findings in the last EULAR recommendations for the contrast agent with respect to healthy subjects [19]. However, the barrier of the costs is still palpable.…”
Section: Introductionmentioning
confidence: 85%
“…Another study from Klauser et al 17 reported data on the relevance of ultrasonography in the diagnosis of sacroiliac inflammatory involvement, adding evidence to the relevance of ultrasound also in diagnostic processes. A study from our group 15 reported another technical contribution for intra-articular ultrasound-guided injection of SIJ, proposing an alternative technical approach for inflammatory SIJ intra-articular therapy.…”
Section: I a L D I S T R I B U T I O N U N A U T H O R I Z E D U S mentioning
confidence: 97%
“…In a later study, the same group used second-generation microbubbles contrast agents for the detection of active sacroiliitis. They measured the depth of the contrast US enhancement in the dorsocaudal part of the SIJ in 42 patients and 21 controls [25]. CEUS showed enhancement depth into the joint cleft of 18.5 mm (range 16-22.1 mm) in all clinically active SIJs, significantly deeper compared to both inactive joints of patients (3.6 mm, range 0-12 mm), and the healthy controls (3.1 mm, range 0-7.8 mm).…”
Section: Sij Dysfunctionmentioning
confidence: 99%
“…However, this modality could encounter difficulties when the joints are too narrow or with many osteophytes, as well as in patients with increased Body Mass Index (BMI). In addition, the application of the contrast itself has a list of contraindications [25].…”
Section: Sij Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation